Modern physics for scientists and engineers - Thornton, Stephen T. (Thomson, Brooks/Cole, 2006)
In addition to featuring the latest discoveries, MODERN PHYSICS presents a contemporary and comprehensive approach to physics with a strong emphasis on applications. The authors discuss the experiments that led to key discoveries in order to illustrate the process behind scientific advances and to give you a historical perspective. A sound theoretical foundation in quantum theory is included to help you succeed in upper division courses.